Investigating the interaction of octapeptin A3 with model bacterial membranes - Han, Mei-Ling (ACS Infect Dis, 2017)
Octapeptins are cyclic lipopeptides that do not exhibit cross-resistance with polymyxins and have a broader spectrum of activity that includes fungi and Gram-positive bacteria. In the present study we investigated the interaction of octapeptin A3 with asymmetric outer membrane models of the Gram-negative pathogen Pseudomonas aeruginosa, using neutron reflectometry, together with fluorimetric and calorimetry methods. For the first time our neutron reflectometry results reveal that the interaction of octapeptin A3 with the Gram-negative outer membrane involves an initial transient polar interaction with the phospholipid and lipid A head groups, followed by the penetration of the entire octapeptin molecule into the fatty acyl core of the outer membrane. This mechanism contrasts that of polymyxin B which specifically targets lipid A, whereas octapeptins appear to target both lipid A and phospholipids. Furthermore, the mechanism of octapeptins does not appear to be highly dependent on an initial complimentary electrostatic interaction with lipid A, which accounts for their ability to bind to the lipid A of polymyxin-resistant Gram-negative bacteria which is modified with cationic moieties that act to electrostatically repel the cationic polymyxin molecule. The presented findings shed new light on the mechanism whereby octapeptins penetrate the outer membrane of polymyxin-resistant Gram-negative pathogens and highlight their potential as candidates for development as new antibiotics against problematic multi-drug resistant pathogens.